Reversible Pancallosal Signal Changes in Febrile Encephalopathy: Report of 2 Cases - Sreedharan, S.E.; Chellenton, J.; Kate, M.P.; Kesavadas, C. (American Journal of Neuroradiology, 2011)
SUMMARY: Transient CC involvement has been reported in encephalopathies/encephalitis of different etiologies. Here we report 2 patients with AFE, who showed transient pancallosal involvement with restricted diffusion on neuroimaging. Both patients had excellent clinical outcomes: The lesion disappeared completely in 1, though there was mild residual gliosis in the other. Serology for dengue virus was positive in 1 of the patients. ADCapparent diffusion coefficientAESDacute encephalopathy with biphasic seizures and late reduced diffusionAFEacute febrile encephalopathyCCcorpus callosumDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryMERSmild encephalitis/encephalopathy with a reversible splenial lesionNAAN-acetylaspartate